Being Unaware of Being HIV-Infected is Associated with Alcohol Use Disorders and High-Risk Sexual Behaviors Among Men Who have Sex with Men in Peru. - Vagenas, Panagiotis; Ludford, Kaysia T; Gonzales, Pedro; Peinado, Jesus; Cabezas, Cesar; Gonzales, Fernando; Lama, Javier R; Sanchez, Jorge; Altice, Frederick L (AIDS and behavior, 2013)
This study compared the correlates of HIV risk among men who have sex with men (MSM) with newly diagnosed versus previously known HIV infection among 5,148 MSM recruited using modified snowball sampling in 5 Peruvian cities. Participants, if age ≥18 years and reporting sex with a male in the previous 12 months, underwent standardized computer-assisted risk assessments and HIV and syphilis testing. Overall, 420 (8.2 %) participants tested HIV seropositive, most of whom (89.8 %) were unaware of their HIV status. Compared to those who knew themselves to be HIV-infected, multivariate logistic regression demonstrated that unprotected anal intercourse at last encounter [AOR = 2.84 (95 % CI 1.09-7.40)] and having an alcohol use disorder (AUD) [AOR = 2.14 (95 % CI 1.01-5.54)] were independently associated with a newly diagnosed HIV infection. Being unaware of being HIV-infected was associated with high-risk sexual behaviors and AUDs, both of which are amenable to behavioral and medication-assisted therapy interventions.